Kennis in meervoud. Voor een ruimhartige wetenschapsgeschiedenis - de Bont, Raf; Wils, Kaat (Studium, 2008)
Knowledge in the plural. For a ‘generous’ history of science  Even if C.P. Snow’s sharp distinction between a scientific and a literary culture has often been contested, historians still mostly conceive these cultures as two separate fields. The authors of this article argue that the potential scope of the history of science is regrettably limited by this dichotomy. Recent developments within the history of science have made clear that scholars of both ‘cultures’ share workplaces, practices and self-images to a large extent, and that even natural scientists heavily rely on artistic representations. The recognition of these commonalities can contribute to a full integration of the human sciences into the history of science and, more generally, into cultural history. This evolution is further stimulated by the transdisciplinary approach which has recently become dominant within the history of the human sciences itself. Since the newly founded journal takes part in these fruitful tendencies, the authors welcome Studium as a promising enterprise.